A Protocol for a Feasibility and Acceptability Study of a Participatory, Multi-Level, Dynamic Intervention in Urban Outreach Centers to Improve the Oral Health of Low-Income Chinese Americans - Mary E. Northridge; Sara S. Metcalf; Stella Yi; Qiuyi Zhang; Xiaoxi Gu; Chau Trinh-Shevrin (Frontiers Media S.A., 2018)
IntroductionWhile the US health care system has the capability to provide amazing treatment of a wide array of conditions, this care is not uniformly available to all population groups. Oral health care is one of the dimensions of the US health care delivery system in which striking disparities exist. More than half of the population does not visit a dentist each year. Improving access to oral health care is a critical and necessary first step to improving oral health outcomes and reducing disparities. Fluoride has contributed profoundly to the improved dental health of populations worldwide and is needed regularly throughout the life course to protect teeth against dental caries. To ensure additional gains in oral health, fluoride toothpaste should be used routinely at all ages. Evidence-based guidelines for annual dental visits and brushing teeth with fluoride toothpaste form the basis of this implementation science project that is intended to bridge the care gap for underserved Asian American populations by improving access to quality oral health care and enhancing effective oral health promotion strategies. The ultimate goal of this study is to provide information for the design and implementation of a randomized controlled trial of a participatory, multi-level, partnered (i.e., with community stakeholders) intervention to improve the oral and general health of low-income Chinese American adults.MethodsThis study will evaluate the feasibility and acceptability of implementing a partnered intervention using remote data entry into an electronic health record (EHR) to improve access to oral health care and promote oral health. The research staff will survey a sample of Chinese American patients (planned n = 90) screened at three outreach centers about their satisfaction with the partnered intervention. Providers (dentists and community health workers), research staff, administrators, site directors, and community advisory board members will participate in structured interviews about the partnered intervention. The remote EHR evaluation will include group adaptation sessions and workflow analyses via multiple recorded sessions with research staff, administrators, outreach site directors, and providers. The study will also model knowledge held by non-patient participants to evaluate and enhance the partnered intervention for use in future implementations.